A square matrix of order n is invertible if there exists a square matrix B of the same order such that AB = In = BA.
In such a case we can say that the inverse of A is B and we write A-1 = B.
Theorem 1.
The inverse of a square matrix exists if |A| ≠ 0.
Proof :
Let A be a matrix of order n and its inverse matrix B will of order n, then
AB = |1|
But |AB| = |A| . |B| = |I| = I
Thus |A| ≠0
Again if |A| ≠ 0 then
\(A\frac{(adjA)}{|A|} = \frac{(adjA)A}{|A|} = I\)
Thus B = \(\frac{(adjA)}{|A|} \) or A-1 (Here B = A-1)
i. e. AB = BA = I
Thus, B inverse matrix of A exists whereas |A| ≠ 0iff |A| ≠ 0.
Theorem 2.
The inverse of non-singular matrix is unique.
Proof :
Let matrix A is a non-singular matrix of order n. B and C are its invertible matrices.
Now AB = BA = I and AC = CA = f
AC = I ⇒ B(AC) = BI = B ...(i)
and BA = I ⇒ (BA)C = CI = C ...(ii)
but B(AQ = (BA)C
(By associativity of multiplication of matrices)
From (i) and (ii), B = C
Thus, invertible matrix has unique inverse.
Theorem 3.
Reversal law of inverse : If A and B are two square matrices of order n and are invertibe then
(AB)-1 = B-1A-1
where A-1 and B-1 are inverse of A and B respectively.
Proof :
A-1 and B-1 are inverse matrices of A and B respectively, then
(AB) (B-1A-1) = A(BB-1)A-1
= AIA-1 (∵ BB-1 = 1)
By associativity of multiplication of matrices
= AA-1 (∵ AI = A)
= I ...(1)
Similarly
(B-1A-1) (AB) = B-1(A-1A)B
= B-1IB (∵A-1A = 1)
By associativity of multiplication of matrices = B-1B (-.IB = B)
= 1 ...(2)
From (1) and (2), we get
(AB)-1 = B-1A-1
Corollary:
(A1A2 ............ An)-1 = An-1An-1.......... A2-1A1-1
Theorem 4.
Cancellation law: If A,B and C are square matrices of order n and A is a non-singular matrix, then
(i) AB = AC => B = C (Left cancellation law)
(ii) BA = CA =>B = C (Right cancellation law)
Proof: Since, A is a non-singular matrix, so A-1 exists.
AB = AC
⇒ A-1(AB) = A-1(AC)
⇒ (A-1aA)B = (A-1A)C [∵ A-1(AB) = (A-1A)B
A-1(AC) = (A-1A)C
By associativity of multiplication of matrices
⇒ IB=IC (∵ A-1A = I)
⇒ B = C (∵ IB = B and IC = C)
Again BA = CA
⇒ (BA)A-1 = (CA)A-1 [∵ (BA)A-1 = B(AA-1)
(CA)A-1 = C(AA-1)
By associativity of multiplication of matrices]
⇒ B(AA-1) = C(AA-1)
⇒ BI = CI (∵ AA-1 = 1)
⇒ B = C (∵ BI = B and Cl = C)
Theorem 5.
If matrix A is invertible then show that transpose of A is also invertible and (A')-1 = (A-1)'.
Proof:
Let A is an invertible matrices of order n, then
∵ |A| ≠ 0
∵ |A'| = |A| ≠ 0
i.e., A' is also invertible,
Now AA-1 = A-1A = I
⇒ (AA-1)' = (A-1A)' = r
⇒ (A-1)'A' =A'(A-1A) = I [∵ (AB)' = B'A' and I' = I
AB = BA = I => B-1 = A]
Thus (A')-1 =(A-1)'
Theorem 6.
If matrix A is invertible and symmetric, then A-1 is also symmetric.
Proof:
A is an invertible symmetric matrix, then A' = A .
Again, we know that
(A-1)' = (A')-1
∴ (A-1)' = A-1 [∵ A' = A]
Thus, A-1 is also symmetric.
Theorem 7.
If A and B are two invertible matrices of same order then show that
(adj AB) = (adj B) (adj A)
Proof:
A and B are invertible matrices of same order, then
|A| ≠ 0 and |B| ≠ 0
∴ |AB| = |A||B| ≠ 0
Thus, (AB)-1 exists.

Thus, adj (AB) = (adj B) (adj A)
Theorem 8.
For any sqaure matrix A, prove that (adj A)' = adj A'
Proof :
Let A be a sqaure matrix of order n. Then (adj A)' and adj A' will be matrices of order n and (i, j)th element of (adj A)'
= (i, j)th element of (adj A)
= Cofactor of (i, j)th element of A
= Cofactor of (j, j)th element of A'
= (i, j)th element of (adj A')
Thus, (adj A)' = (adj A').
Theorem 9.
If A be a non-singular matrix of order tt then show that
|adjA| = |A|n-1.
Proof:
∵ A (adj A) = |A| I
⇒ |A (adj A) | = |A| |I| (∵ A = B ⇒ |A| = |B|)
⇒ |A| |adjA| = |A|n |I| [∵ |kI| = knI]
⇒ |A| |adj A| = |A|n
⇒ |adjA| = |A|n-1 [∵ |I| = I]
Thus, |adjA| = |A|n-1.
Theorem 10.
If matrix A is non-singular matrix of order n, then show that
adj (adjA) = |A|n-2A .
Proof:
We know that for any non-singular matrix B.
B(adj B) = |B|I
Let B = adj A
Then (adj A) [adj (adj A)] = |adj A| I
⇒ (adj A) [adj (adj A)] = | A |n-1I [∵ (adjA) = |A|n-1]
⇒ A(adj A) [adj (adj A)] = |A|n-1A [∵ AIn = A]
⇒ |A| [adj (adj A)] = |A|n-1A [∵ A (adj A) = |A| I]
⇒ [adj (adj A)] = | A |n-2A
Corollary: If matrix A is a non-singular matrix of order n, then
| adj (adj A) | = |A|(n-1)2
Proof:
∵ adj (adj A) |A|n-2 (By Theorem 10)
⇒ |adj (adj A)| = || A |n-2A|
⇒ |adj (adj A)| = | A |n(n-2) |A| (∵ |kA| = kn|A|)
⇒ |adj (adjA)| =An2-2K + 1 (|A|n(n-2) A| = | A |n2-2K + 1]
⇒ |adj (adj A)| =A(n-1)2